Screening and Preventative Strategies for Patients at High Risk for Breast Cancer. Issue 4 (April 2021) - Ter-Minassian, Monica; Schaeffer, Marcy L.; Jefferson, Celeena R.; Shapiro, Stacey C.; Suwannarat, Pim; Visvanathan, Kala
Abstract : PURPOSE: Current US guidelines recommend more intensive breast cancer screening and preventive strategies for patients at more than 20% lifetime risk for breast and ovarian cancer (high risk for breast and ovarian cancer [HRBOC]). Guidelines recommend that yearly mammograms alternating with magnetic resonance imaging (MRI) screening should be considered as early as 30 years old. Furthermore, BRCA mutation carriers should consider bilateral mastectomy and bilateral oophorectomy after age 35. It was unclear what the uptake of screening and risk-reducing strategies were for patients who were cancer-free and cancer survivors seen by Kaiser Permanente Mid-Atlantic States (KPMAS) Genetics. METHODS: We retrospectively studied female patients (members of KPMAS between 2005 and 2016) diagnosed as HRBOC and/or tested for breast cancer-related mutations by KPMAS Genetics during 2013-2016. We identified cancer diagnoses, mammogram and breast MRI screening, mastectomies, and oophorectomies that occurred before and after the Genetics visit during the study period. RESULTS: Our cohort included 813 women with a HRBOC diagnosis, with a median 51 years of age at diagnosis, 45% White, 38% Black, and 15% other ethnicity. Most cancers occurred prior to the Genetics visit: 513/527 breast cancer diagnoses and 55/57 ovarian cancer diagnoses. Fewer than five prophylactic mastectomies and 89 prophylactic oophorectomies were identified. Among 228 patients who were 30-75 years old, breast cancer–free at the time of HRBOC diagnosis, and members for over 6 months, 190 (83%) had at least one screening test (mammogram or MRI) after the consultation with Genetic, but 79% never had an MRI before or after the consultation. CONCLUSION: Our findings suggest that earlier detection of patients with HRBOC and closer monitoring is needed.